Comparison between triamcinolone injection and hydrocortisone injection in treatment of trigger finger: a prospective single-blinded randomized controlled study - Mohd Ramli, Radzeli (2011)
Trigger finger is a term for stenosing tenovaginitis affecting the excursion of the long flexor of the hand at the area of zone II of the digit. Steroid injection is one of the treatment option. Triamcinolone is the steroid mainly used for trigger finger treatment. Hydrocortisone is used only in paeditric trigger finger. Therefore result and outcome of hydrocortisone in treatment of adult trigger finger still not establish. PURPOSE: This study was designed to test the null hypothesis that there is no difference in resolution of trigger finger in term of pain, tenderness and triggering/locking in 3 months after injection with triamcinolone, a depot form of potent steroid or hydrocortisone, a highly soluble form but less potent steroid. METHODS: Seventy patients were enrolled in a prospective randomized controlled study comparing triamcinolone and hydrocortisone injection for idiopathic trigger finger. They were randomized into two groups; triamcinolone group and hydrocortisone group. All patients required to answer DASH questionnaire, give VAS score and evaluated for triggering/locking and tenderness at A1 pulley before injection, immediately after injection and 3 months after injection. Fifty-nine patients completed the 3 months follow-up (28 triamcinolone arm, 31 dexamethasone arm). Outcome measures included the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire, presence/absence of triggering/locking finger, presence/absence of A1 pulley tenderness and pains severity base on visual analog scale. A Chi-square test and student t-test were used to compare both groups. RESULTS: Immediately after injection, absence of triggering was documented in 24 of 34 patients (70.6%) in the triamcinolone group and in 28 of 36 patients (77.8%) in the hydrocortisone group. The rates of resolution of triggering 3 months after injection were 22 of 28 (78.6%) in the triamcinolone group and 26 of 31 (83.9%) in the hydrocortisone group. In term of tenderness of A1 pulley, immediately after injection, absence of tenderness was documented in 26 of 34 patients (76.5%) in the triamcinolone group and in 28 of 36 patients (77.8%) in the hydrocortisone group. The rates of resolution of tenderness 3 months after injection were 18 of 28 (64.3%) in the triamcinolone group and 22 of 31 (71%) in the hydrocortisone group. There were no significant differences between Disabilities of the Arm, Shoulder, and Hand scores and Visual Analog Scale score for pain immediately after injection and the 3-month follow-up. After the close of the study, there was no complication in both treatment groups. CONCLUSIONS: There is no significant different in term of resolution of tenderness over A1 pulley, resolution triggering/locking, pain and physical disabilities score improvement between the two types of steroid injection.